Multidimensional Connectivity : Why the Interplay of International Connections Matters for Knowledge Transfers - Gould, David M.; Panterov, Georgi (Elsevier, 2018)
Globalization has increased exponentially since the mid-twentieth century with the advent shipping containers, digital technologies and air transport. Being well-connected has important implications not only for incomes, but the transfer of ideas and growth enhancing technology. This study finds that being connected to well-connected countries matters for economic growth, but there is complementarity in the various types connections that enhances growth as well. Countries can benefit from: (i) multiple types of economic links (such as trade, investment, migration, and modern telecommunications) that underpin the movement of technologies and ideas; but also, (ii) the quality of connections in terms of knowledge spillovers and the indirect connections made through partners that are well connected. These are both aspects of inter-connectedness that have implications for growth and growth spillovers.